The effects of perceived crowding, emotional dissonance, and emotional exhaustion on critical job outcomes: A study of ground staff in the airline industry - Karatepe, Osman M.; Choubtarash, Homa (Elsevier Sci Ltd, 2014)
Using Conservation of Resources (COR) theory and Stressor-Strain-Outcome (SSO) model as the theoretical underpinnings, this study proposes and tests a research model that examines emotional exhaustion as a mediator of the impact of emotional dissonance on service recovery performance, turnover intentions, and absenteeism. The model also investigates the mediating role of emotional dissonance in the relationship between perceived crowding and emotional exhaustion. Data obtained from ground staff in the low cost airline industry in Turkey were used to gauge these relationships. The results from structural equation modeling suggest that passenger crowding as perceived by ground staff results in emotional dissonance that in turn heightens emotional exhaustion. The results further suggest that emotional exhaustion fully mediates the effect of emotional dissonance on turnover intentions and absenteeism. Interestingly, the results suggest that the impact of emotional dissonance on service recovery performance, mediated by emotional exhaustion, is positive. Theoretical and management implications based on the aforesaid findings are discussed in the paper. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Emotional dissonance; Emotional exhaustion; Ground staff; Low cost airlines; Perceived crowding; Job outcomes